Kelayakan Pembangunan Gudang Pusat Distribusi Provinsi (PDP) Jawa Barat Ditinjau Dari Aspek Keuangan - Setiajatnika, Eka; Gunadi, Trida (Departement Of Accounting, Indonesian Cooperative Institute, Indonesia, 2021)
The purpose of this study was to analyze the feasibility of building a Provincial Distribution CenterWarehouse (PDP) in Purwakarta Regency, West Java from a financial / financial aspect. The results ofthe analysis show that the investment cost for the construction of a PDP warehouse is IDR 23.7 billion,the return on investment (Payback Period) is short, namely 5 years 8 months, the Net Present Value isPositive, which is 3,080,408 and the Profitability of Index is greater than 1, namely 1 , 00013, then theplan to build a Provincial Distribution Center Warehouse in Campaka District, Purwakarta Regency isfeasible / feasible.